Toward Valid Measurement of (Un)fairness for Generative AI: A Proposal for Systematization Through the Lens of Fair Equality of Chances - Truong, Kimberly Le; Zimmermann, Annette; Heidari, Hoda (Proceedings of the AAAI/ACM Conference on AI, Ethics, and Society, 2025)
Disparities in the societal harms and impacts of Generative AI (GenAI) systems highlight the critical need for effective unfairness measurement approaches. While numerous benchmarks exist, designing valid measurements requires proper systematization of the unfairness construct. However, this process is often neglected, resulting in metrics that may mischaracterize unfairness by overlooking contextual nuances, thereby compromising the validity of the resulting measurements. Building on established (un)fairness measurement frameworks for predictive AI, this paper focuses on assessing and improving the validity of the measurement task. By extending existing conceptual work in political philosophy, we propose a novel framework for evaluating GenAI unfairness measurement through the lens of the Fair Equality of Chances framework. Our framework decomposes unfairness into three core constituents: the harm or benefit resulting from the system outcomes, morally arbitrary factors that should not lead to inequality in the distribution of harm or benefit, and the morally decisive factors, which distinguish subsets that can justifiably receive different treatments. By examining fairness through this structured lens, we integrate diverse notions of (un)fairness while accounting for the contextual dynamics that shape GenAI outcomes. We analyze factors contributing to each component and the appropriate processes to systematize and measure each in turn. This work establishes a foundation for developing more valid (un)fairness measurements for GenAI systems.